Design Violence Reporting System Households in Mataram City - Tria Ningrum, Farah; Nadiyasari Agitha; Noor Alamsyah (Journal of Computer Science and Informatics Engineering (J-Cosine), 2023)
Currently, cases of domestic violence are social and humanitarian problems that need attention. In 2020, the most dominant forms of domestic violence are psychological violence as much as 40%, sexual violence 26%, physical violence 22%, and economic 12%. The number of domestic violence cases in Indonesia also increased in 2019 from 1,419 cases to 2,389 cases in 2020. The increasing number of cases of domestic violence should be a serious concern for all parties. The Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA) is a regional technical implementing unit formed by the regional government that can provide services for women and children who experience domestic violence, services, special protection, consultation, and others. The process of reporting domestic violence in Mataram City is still done conventionally, where people still need to visit the office to report incidents of domestic violence. Then the UPTD PPA will conduct a team discussion for the next action. From the current reporting process flow, the Mataram City UPTD PPA also still takes a long time to follow up on the domestic violence report. So there is still a lack of facilities and media that can assist the community in reporting domestic violence and assist the UPTD PPA in following up on reporting domestic violence. With the development of existing technology and the increasing number of people using android gadgets, from the problems above, researchers will design and build a Domestic Violence Reporting System in the City of Mataram to make it easier to report domestic violence directly without having to go to the authorities to handle the problem. The method that will be used for the development of this system is the Extreme Programming (XP) method.